Analisis Tingkat Kecemasan Matematika Mahasiswa Pada Mata Kuliah Kapita Selekta Matematika - Rabiatul Aeprilia Nuraisyah; Hasanuddin Hasanuddin (GLOBAL SCIENTS PUBLISHER, 2026)
Mathematics is a field of study that plays a vital role in daily life and in the world of education. However, in the process of learning mathematics, not all students are able to keep up effectively due to affective factors, one of which is math anxiety. This study aims to analyze the level of math anxiety among Mathematics Education students in the “Selected Topics in Mathematics” course. This study employs a descriptive method with a quantitative approach. The research subjects were 25 students from the Mathematics Education Program at UIN Sultan Syarif Kasim Riau, selected using purposive sampling. The research instrument consisted of a mathematics anxiety questionnaire comprising 20 statements on a four-point Likert scale. Data analysis utilized descriptive statistics, including mean, standard deviation, and percentage. The results showed that the average mathematics anxiety score of the students was 46.84, which falls into the low category, with a standard deviation of 6.562. The data distribution indicated that 72% of students were in the low category, 24% in the high category, and 4% in the very low category, while 0% of students were in the very high category. Thus, it can be concluded that the level of students’ mathematics anxiety in the Kapita Selekta Mathematics course is classified as low, although there are still some students who experience anxiety in the high category.